1994
DOI: 10.1017/s0317167100041263
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Mitoxantrone in Multiple Sclerosis: Serial MRI Evaluation at One Year

Abstract: Abstract:We present the results of a randomized double-blinded placebo controlled, multicenter trial, of low-dose mitoxantrone (MX), after one year, in 25 patients with relapsing-remitting multiple sclerosis, who had serial enhanced magnetic resonance imaging (MRI). Treatment groups were balanced for age, gender, duration of illness and neurological disability. Five of the 13 MX patients and 10 of the 12 placebo patients had exacerbations during treatment (p < 0.02). The mean change in the extended disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 23 publications
(16 reference statements)
0
13
0
1
Order By: Relevance
“…In fact, benefit can be seen in disease progression in patients with secondary progressive MS (SPMS) 1 3 -1 5 . Randomized studies has also showed reduction of relapsing and new lesions incidence using magnetic resonance imaging (MRI) [16][17][18] . Mitoxantrone (MX) acts as an immunosupressive agent which alters B and T lymphocytes responses to central nervous system (CNS) antigens, and through this process it seems to avoid axonal lesion and macrophages mediated demyelination [1][2][3][4][5][6][7][8][9]13,19 .…”
Section: Mitoxantrone Hydrochloride (Novantronementioning
confidence: 99%
“…In fact, benefit can be seen in disease progression in patients with secondary progressive MS (SPMS) 1 3 -1 5 . Randomized studies has also showed reduction of relapsing and new lesions incidence using magnetic resonance imaging (MRI) [16][17][18] . Mitoxantrone (MX) acts as an immunosupressive agent which alters B and T lymphocytes responses to central nervous system (CNS) antigens, and through this process it seems to avoid axonal lesion and macrophages mediated demyelination [1][2][3][4][5][6][7][8][9]13,19 .…”
Section: Mitoxantrone Hydrochloride (Novantronementioning
confidence: 99%
“…In addition, in a subgroup of patients (13 MTX and 12 placebo) a serial enhanced MRI study was performed at 0, 2, 4, 6 and 12 months from the beginning of the study [1].…”
Section: Safety Evaluationmentioning
confidence: 99%
“…22 All patients had RRMS with at least two attacks in the 2 years preceding study entry. The mean EDSS score was 3.7 in the treated group and 3.5 in the placebo group.…”
mentioning
confidence: 99%